The Application of Software’s in Cost Estimation for Quantity Surveyor - Ting, How Ann; Nurulhuda, Ahamad (2016)
The construction industry in Malaysia has been seen as the most problematic industry such as over budget, delay, the production of low quality product, intensive labour as well as still using yesteryears technology. The aim of this research was to investigate the utilization or application of softwares in cost estimation for quantity surveyor. The study shows that method of estimation process and experience of quantity surveyor help to obtain accurate results. In conclusion, the used of software helps to solve most of the problem occur in construction industry.